Future Prospects of the Assembly Model for MEP Systems in Chinese Buildings: A Whole Life Cycle Perspective - Chun Wang; Peng Ouyang; Xiaodong Liu; Zhihua Zou; Yuanping Wang; Ruiling Wang (Applied Sciences)
The assembly building M&E (Monitoring and Evaluation) system is a vital part of the transformation of China’s construction industry, featuring intelligent control, high efficiency, and high safety. The article provides a comprehensive review of research related to assembly M&E systems from the perspective of the whole life cycle of assembly, containing 125 journal articles from 1993 to 2024. The article analyzes some policies with updated iterations in the United States, Japan, Germany, Denmark, France, and the European Union. The literature review and semi-structured interviews with experts identified significant constraints limiting the various stages of the entire life cycle of assembled MEP (mechanical, electrical, and plumbing) systems. The absence of uniform design standards, personnel collaboration, prefabricated component testing, transportation, information utilization, intelligent testing, and recycling of disassemblability that can occur in the entire life cycle of assembled MEP systems are summarized. Finally, the article suggests that assembly M&E systems can be shared and marketed to improve the economic viability of assembly M&E systems and their wide application in the areas of technology, platform, and demand.